(untitled) (Research, Society and Development, 2022)
The study addresses the issue of a professional aged 30 years with suspected ADHD. This is a concept that draws the attention of researchers in the context of inclusive education. It is noticed that in Brazil a paradox exists between what the laws preach and what is actually carried out in practice. Companies are not yet prepared to deal with professionals who have these characteristics. Thus, this article aimed to address the challenges of professional inclusion of a person with ADHD. Thus, it was a bibliographic, qualitative, exploratory and explanatory study, which are part of the methodological framework of the study. Data mining was carried out in the Digital Library of Theses and Dissertations, scientific articles and other academic media. The study showed as results: a) the existence of characteristics of a professional who shows some characteristics of ADHD. And with regard to the conclusions, the study can conclude that the theme of ADHD in organizations needs to be further discussed in terms of its debate and suggests the participation of the family and other professionals who act as satellites to this patient, as a way of making professional inclusion in all decision-making processes of the organization is more fruitful. The biggest challenge for a company is an inclusive bias is to guarantee access and permanence of these professionals in all existing processes in companies, with a view to achieving greater efficiency in their various professional activities, in addition to having and exercising all their citizen rights.